1998
DOI: 10.1007/bf01759378
|View full text |Cite
|
Sign up to set email alerts
|

On deformable hypersurfaces in space forms

Abstract: [Bil ]. A few years after SBRANA, CARTAN (1) published similar results but in the language of envelopes of hyperplanes.Deformable hypersurfaces can be divided into four classes. Submanifolds belonging to the two less interesting ones, namely, surface-like and ruled hypersurfaces, are highly deformable. On the contrary, while hypersurfaces in one of the remaining classes admit, precisely, a continuous one-parameter family of isometric deformations, elements belonging to the other class have a unique one.The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…Note that if M n is simply-connected then the set of all isometric immersions of M n into R n+1 consists of ruled immersions with the same rulings; see [5]. Moreover, this set can be parametrized by the set of all smooth functions in an interval.…”
Section: The Ruled Casementioning
confidence: 99%
“…Note that if M n is simply-connected then the set of all isometric immersions of M n into R n+1 consists of ruled immersions with the same rulings; see [5]. Moreover, this set can be parametrized by the set of all smooth functions in an interval.…”
Section: The Ruled Casementioning
confidence: 99%
“…A modern account of the classification of Sbrana-Cartan hypersurfaces was given in, 12 where also some questions left open in the works by Sbrana and Cartan were answered, as the existence of hypersurfaces of the discrete type and the possibility of gluing together hypersurfaces of distinct classes.…”
Section: Local Theory For the Isometric Casementioning
confidence: 99%
“…The classification of Sbrana-Cartan hypersurfaces was extended to the case of nonflat ambient space forms by Dajczer-Florit-Tojeiro [9]. Moreover, among other things, in that paper it was given an affirmative answer to the question of whether Sbrana-Cartan hypersurfaces that allow a single deformation do exist, which was not addressed by Sbrana and Cartan. A nonparametric description of Cartan hypersurfaces of dimension n ≥ 5 was given in [13], where it was shown that any such hypersurface arises by intersecting the light-cone V n+2 in Lorentzian space L n+3 with a flat space-like submanifold of codimension two of L n+3 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among other things, in that paper it was given an affirmative answer to the question of whether Sbrana-Cartan hypersurfaces that allow a single deformation do exist, which was not addressed by Sbrana and Cartan. A nonparametric description of Cartan hypersurfaces of dimension n ≥ 5 was given in [13], where it was shown that any such hypersurface arises by intersecting the light-cone V n+2 in Lorentzian space L n+3 with a flat space-like submanifold of codimension two of L n+3 . We refer to [9] and [13], respectively, for modern accounts of the classifications of Sbrana-Cartan and Cartan hypersurfaces.…”
Section: Introductionmentioning
confidence: 99%